Recruiting care homes to a randomised controlled trial - Ellwood, Alison; Airlie, Jennifer; Cicero, Robert; Cundill, Bonnie; Ellard, David R; Farrin, Amanda; Godfrey, Mary; Graham, Liz; Green, John; McLellan, Vicki; Siddiqi, Najma; Forster, Anne (Current controlled trials in cardiovascular medicine, 2018)
Background There are more than a quarter of a million individuals aged ≥ 65 years who are resident in care homes in England and Wales. Care home residents have high levels of cognitive impairment, physical disability, multimorbidity and polypharmacy. Research is needed to ensure there are robust, evidence-based interventions to improve the quality of life of this frail group. However, there is a paucity of research studies in this area. Recruiting care homes and their residents to research is challenging. A feasibility, cluster randomised controlled trial was undertaken as part of a research programme to identify ways to develop and test methods to enhance the physical activity of care home residents. This paper describes two methods of recruiting care homes to the trial and draws out learning to inform future studies. Methods Eligible care homes met the following criteria: they were within a defined geographical area in the north of England; provided residential care for adults ≥ 65 years of age; had not previously been involved in the research programme; were not taking part in a conflicting study; were not recorded on the Care Quality Commission website as ‘inadequate’ or ‘requiring improvements’ in any area; and had ≥ 10 beds. Care homes were identified by a ‘systematic approach’ using the Care Quality Commission website database of care homes or a ‘targeted approach’ via a network of research-ready care homes. A standardised method was used to recruit care homes including eligibility screening; invitation letters; telephone contact; visits; formal letter of agreement. Results In the systematic approach, 377 care homes were screened, 230 (61%) were initially eligible and invited to participate, 11 were recruited (recruitment rate (RR) 4.8%). In the targeted approach, 15 care homes were invited to participate, two were recruited (RR 13.3%). Overall, 245 care homes were approached and 13 recruited (RR 5.3%). A variety of care homes were recruited to the trial in terms of size, location, ownership and care provision. Conclusions Systematic recruitment of care homes to the study was time-consuming and resource-heavy but led to a variety of care homes being recruited. The targeted approach led to a higher recruitment rate. Trial registration ISRCTN registry, ISRCTN16076575 . Registered on 25 June 2015.